Relationship of Brain Glutamate Response to D-Cycloserine and Lurasidone to Antidepressant Response in Bipolar Depression: A Pilot Study - Dong, Zhengchao; Grunebaum, Michael F.; Lan, Martin J.; Wagner, Vashti; Choo, Tse-Hwei; Milak, Matthew S.; Sobeih, Tarek; Mann, J. John; Kantrowitz, Joshua T. (Frontiers in Psychiatry, 2021)
Introduction: N-methyl-D-aspartate glutamate-receptor (NMDAR) antagonists such as ketamine have demonstrated efficacy in both major depressive disorder (MDD) and bipolar disorder depression (BP-D). We have previously reported that ketamine-induced reduction in Glx (glutamate + glutamine), measured by proton magnetic resonance spectroscopy (1H MRS) during the ketamine infusion, mediates the relationship of ketamine dose and blood level with improvement in depression. Methods: In the present study, we assessed the impact on glutamate and Glx of a combination of D-cycloserine (DCS), an NMDAR antagonist when used at higher doses (>500 mg), combined with lurasidone in BP-D. Subjects with DSM-V BP-D-I/II and a Montgomery-Asberg Depression Rating Scale (MADRS) score>17, underwent up to three 1H MRS scans. During Scan 1, subjects were randomized to receive double-blind lurasidone 66 mg or placebo. During Scan 2, all subjects received single-blind DCS 950 mg + lurasidone 66 mg, followed by 4 weeks of open label phase of DCS+lurasidone. Results: Five subjects received lurasidone alone and three subjects received placebo for Scan 1. Six subjects received DCS+lurasidone during Scan 2. There was no significant baseline or between treatment-group differences in acute depression improvement or glutamate response. In Scan 2, after a dose of DCS+lurasidone, mean change in glutamate correlated negatively with improvement from baseline MADRS (r=-0.83, p=0.04). There were no unexpected adverse events. Conclusions: These pilot results require replication but provide further support for a link between antidepressant effect and a decrease in glutamate by the NMDAR antagonist class of antidepressants.